Transformasi Amanat Lakon Ramayana dalam Seni Pertunjukan Wisata Indonesia –Thailand - Robby Hidajat; Surasak Jamnongsarn; Muhammad Afaf Hasyimy (Institut Seni Indonesia Denpasar, 2022)
The background of this research is to answer the hesitance regarding the moral messages in tourism performance art. The moral messages in tourism performance art that plays Ramayana story is then analyzed. Ramayana story is presented in tourism performance art in Indonesia and Thailand. In the beginning, Ramayana story is functioned to be the guidance for the audiences to learn about moral ethics from the character, structure, and appearance of the presentation. Ramayana story is now presented mostly for tourism entertainment but Educative Mandate is still conserved in tourism performance art. The design of this research is qualitative descriptive with functional approach. Data collection method involves interview and observation. Key informants are dancer, musician, tourism performance organizer, and art teacher in art school that represent Indonesia and Thailand. Observation was conducted on the centers of tourism performance art in Yogyakarta and Denpasar, Indonesia and also in Bangkok, Thailand. Results of research showed that (1) Mandate of Romance refers to the romance life of the characters in Ramayana story; (2) Mandate of Woman Paragon considers woman as both strength and weakness of man; and (3) Mandate of Causal Law emphasizes that the wrong is lost and the right is won.